PENGARUH HARGA, KUALITAS PRODUK, DAN WORD OF MOUTH (WOM) TERHADAP KEPUTUSAN PEMBELIAN DENGAN CITRA MEREK (OLI SHELL ADVANCE) SEBAGAI VARIABEL INTERVENING PADA PENGGUNA SHOPEE DI SITUBONDO - Erdyansyah Setiawan; Ediyanto Ediyanto; Randika Fandiyanto (Fakultas Ekonomi dan Bisnis, 2025)
The purpose of this study is to analyze The Influence of Product Quality Price and Word of Mouth (WOM) on Purchasing Decisions with Brand Image (Shell Advance Oil) as an Intervening Variable on Shopee Users in Situbondo. Using the Partial Least Square (PLS) Structural Equation Model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application Price has a significant positive effect on brand image,Product quality has a significant positive effect on brand image.,Word of Mouthhas a significant positive effect on brand image, Price has a significant positive effect on purchasing decisions, Product quality has a significant positive effect on purchasing decisions.,Word of Mouthhas a positive but not significant effect on purchasing decisions, Brand image has a significant positive influence on purchasing decisions, Price has a significant positive effect on purchasing decisions through brand image., Product quality has a positive but not significant effect on purchasing decisions through brand image., And Word of Mouthhas a significant positive influence on purchasing decisions through brand image.